Skintific Purchase Decisions Among TikTok Users in Purwokerto: The Role of Influencer Marketing, e-WOM, Brand Image, and Product Quality - M Rizki Bahtiar; Totok Haryanto Totok Haryanto; Erny Rachmawati; Hengky Widhiandono (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the influence of consumer purchasing decisions of Skintific skincare products in Purwokerto with the variables of influencer marketing, electronic word of mouth, brand image, and product quality. Quantitative data collection using Google Forms with a Likert Scale of 1-5. The research population is residents of Purwokerto who have purchased Skintific skincare products and are actively using TikTok. Sampling used a non-probability method with a purposive sampling technique. The Lemeshow method was used to determine the minimum number of samples and and the final sample consisted of 130 respondents. This study uses the Construct Validity and Reliability Test, Discriminant Validity of Fornell-Larcker and HTMT criteria, Inner VIF, Model Fit, R-Square and Hypothesis Test. The data were analyzed using the SmartPLS 3. The results of this study showed that all variables were positively related to purchase decisions, influencer marketing (β=.334), electronic word of mouth (β=.276), brand image (β=.357), and product quality (β=.306), all p<.001; R²=.643. In this study, all variables can influence purchasing decisions with the findings of brand image as the variable that has the highest influence. The findings indicate the importance of brand image consistency in Skintific communication on TikTok. This study contributes to the digital marketing literature by providing empirical evidence on the effects of influencer marketing, e-WOM, brand image, and product quality on purchase decisions. However, this study is limited to TikTok users in Purwokerto.